Medical Acts and Conscientious Objection: What Can a Physician be Compelled to Do?. Issue 3 (3rd July 2019) - Gamble, Nathan K.; Pruski, Michal
Abstract : A key question has been underexplored in the literature on conscientious objection: if a physician is required to perform 'medical activities, ' what is a medical activity? This paper explores the question by employing a teleological evaluation of medicine and examining the analogy of military conscripts, commonly cited in the conscientious objection debate. It argues that physicians (and other healthcare professionals) can only be expected to perform and support medical acts – acts directed towards their patients' health. That is, physicians cannot be forced to provide or support services that are not medical in nature, even if such activities support other socially desirable pursuits. This does not necessarily mean that medical professionals cannot or should not provide non-medical services, but only that they are under no obligation to provide them.